أثر نشاط صناديق الإستثمار التقليدية و الإسلامية على الأسواق السعودية - بودكارة, سهام (My University, 2022)
The financial market is a meeting place for money offerors and money seekers, in which various securities are traded through the mediation of specialists and under the supervision of public authorities. The financial markets are classified into several types according to criteria that vary from one classification to another. They are divided according to the issuance and trading criterion into primary and secondary markets, and according to the criterion of the terms of operations into cash markets and capital markets, and according to the term of execution of operations, they are divided into Present and future markets
دراسة حالة الاسواق الخليجية
Keywords: The financial market, the employment of liquidity, the control of public authorities, the offerors and seekers of funds, the dealers